2020
DOI: 10.21203/rs.3.rs-25100/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypertension prevalence, awareness, treatment, and control and predicted 10-year CVD risk: a cross-sectional study of Seven Communities in East and West Africa (SevenCEWA)

Abstract: Background: Few studies have characterized the epidemiology and management of hypertension across several communities with comparable methodologies in sub-Saharan Africa. We assessed prevalence, awareness, treatment, and control of hypertension and predicted 10-year cardiovascular disease risk across seven sites in East and West Africa. Methods: Between June and August 2018, we conducted household surveys among adults aged 18 years and above in 7 communities in Kenya, Nigeria, Tanzania, and Uganda. Following a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…We hypothesize the higher proportion to the increased prevalence of multiple cardiovascular risk factors in our cohort: diabetes mellitus, hypertension, obesity and cigarette smoking. These factors are considered silent preventable killers and the main reasons for premature CAD globally and in SSA, with higher prevalence noted in the East African region (37)(38)(39). These observations support the present-day emphasis on controlling risk factors and quitting cigarette smoking to prevent adult coronary artery disease.…”
Section: Discussionmentioning
confidence: 59%
“…We hypothesize the higher proportion to the increased prevalence of multiple cardiovascular risk factors in our cohort: diabetes mellitus, hypertension, obesity and cigarette smoking. These factors are considered silent preventable killers and the main reasons for premature CAD globally and in SSA, with higher prevalence noted in the East African region (37)(38)(39). These observations support the present-day emphasis on controlling risk factors and quitting cigarette smoking to prevent adult coronary artery disease.…”
Section: Discussionmentioning
confidence: 59%
“…Several studies indicate that 44% to 93% of individuals within SSA are unaware of their hypertensive status. 2,6,8,9 This phenomenon underscores a labyrinth of barriers, including limited access to health care, 10 lack of health care infrastructure, 11 lack of screening programs, 12 demographic factors, 13 low health literacy, 14 the specter of stigma, 15 and the impact of cultural beliefs 16 (Figure 2). Potential solutions may involve utilizing telemedicine and mobile health services to expand medical access to remote regions.…”
Section: Underdiagnosing Hypertension and Hdp In Ssamentioning
confidence: 99%
“…Many risk factors are on the rise in SSA due to changing lifestyles including increases in sedentary behaviors, cigarette smoking, and alcohol consumption. 2,8,37 A Uganda study found that 61.6% of individuals report spending their work time sitting or standing without engaging in any physical activity lasting more than 10 minutes per day. 38 Additionally, 68.7% of their leisure time was spent in a sedentary manner.…”
Section: Underdiagnosing Hypertension and Hdp In Ssamentioning
confidence: 99%
See 2 more Smart Citations